2017
DOI: 10.1111/scs.12532
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing patient safety in the operating theatre: from the perspective of experienced operating theatre nurses

Abstract: Constantly managing risk and preventing the OT patient from harm is essential according to the experienced OTNs, who are in a key position to identify threats to patient safety and should be empowered to enhance patient safety as a constant endeavour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
(57 reference statements)
0
20
0
8
Order By: Relevance
“…Baillie and Ilott () emphasizes to restore patient dignity and pay attention to colleagues, regardless of status, of their behaviour. Ingvarsdottir and Halldorsdottir () means, it is important to speak up even if such comments were not well‐received. Another study showed how OTNs preserved patient dignity through being present for each other and caring for the patient in perioperative practice (Blomberg, Bisholt, et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baillie and Ilott () emphasizes to restore patient dignity and pay attention to colleagues, regardless of status, of their behaviour. Ingvarsdottir and Halldorsdottir () means, it is important to speak up even if such comments were not well‐received. Another study showed how OTNs preserved patient dignity through being present for each other and caring for the patient in perioperative practice (Blomberg, Bisholt, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…() describe that the OTNs responsibility is to retrieve information from and about the patient, which influence planning prior to surgery and help control the situation and increase preparedness for unforeseen events. Ingvarsdottir and Halldorsdottir () conducted interviews with experienced OTNs that showed how they took responsibility for the patient's vulnerability and safely navigated the patient through the nursing process. Arakelian, Swenne, Lindberg, Rudolfsson, and Vogelsang () study emerged that the patients perceived that they were respected as a person, taken seriously and participated in their care if it was carried out in a person‐centred manner.…”
Section: Introductionmentioning
confidence: 99%
“…Communication in the context of health work is important to provide information, exchange experiences, persuade in order to generate behavior changes and discuss the most varied subjects (19) . However, because it is a closed working environment with several professional categories, the occurrence of communication problems and relationship conflicts is common in the operating room, especially among medical and nursing staff, since historically the medical team has a tendency to place itself in a hierarchically superior position to the nursing team (26)(27) . In this context, nurses play an important mediating role to promote integration between professionals and conflict resolution (3,27) .…”
Section: Development Of Continuing Education Actionsmentioning
confidence: 99%
“…Participants also scored in Class 5 on the importance of increasing nurse autonomy in the operating room. The autonomy of the nurse is important for him to apply measures of risk management and prevention of harm to the patient as soon as this is necessary in the operating room (26,33) . In addition, autonomy assists in the satisfactory development of nurses' activities in relation to the management of nursing care and the work of the multiprofessional team (3,26) .…”
Section: Development Of Continuing Education Actionsmentioning
confidence: 99%
“…For the perioperative nurse (operating room nurse or nurse anaesthetist), managing risks and preventing postoperative complications are fundamental elements in perioperative nursing care (Ingvarsdottir & Halldorsdottir, 2017;Niu, Li, Tang, Gong, & Zhang, 2017). Positioning the patient on the operating bed is one important task for the perioperative nurse with the goal to maintain optimal circulation and protect muscles, nerves and bony prominences from pressure injury (Hortman & Chung, 2015).…”
Section: Preventive Perioperative Nursing Carementioning
confidence: 99%